Acritarchs of peri-Gondwana at the Lower and Middle Ordovician stage boundaries - Li, Jun (2003)
Although acritarchs have been studied mostly for stratigraphic purposes (often in sediments devoid of other fossils), their biostratigraphic potential has not yet been fully exploited in the Ordovician. While another group of palynomorphs, the chitinozoans, have become increasingly important in international correlations, the acritarchs continue to play a minor role in Ordovician biostratigraphy. Today, about 1000 papers deal with Ordovician acritarchs, most of which are published by scientists working in Europe. The geographical areas studied in detail are in Europe and North Africa (Servais et al., in press). Investigations of Laurentian acritarchs are generally limited to the upper Middle Ordovician and the Upper Ordovician. Apart from two publications with detailed descriptions, studies from Australia are almost non–existant. In recent years, an increasing number of investigations have been carried out in China (Li et al., 2002) and South America (e.g., Rubinstein and Toro, 2001). However, at a global scale, many areas remain almost unstudied. Palaeobiogeographically, two distinct geographic acritarch assemblages can be recognized in the Lower–Middle Ordovician. A first assemblage (also named "province"), in the upper Tremadocian in low latitude areas, was attributed to warm–water environments, and a second assemblage, successively named "Mediterranean" or "peri–Gondwanan province", can easily be recognized around the southern border of Gondwana, from Argentina through north Africa and peri–Gondwana to Iran, Pakistan and southern China (Vavrdová, 1974; Li and Servais, 2002). Over 250 genera and over 1500 species of Ordovician acritarchs have been described so far (Servais et al., in press). Among the more than 500 acritarch species described from peri–Gondwana, some may be used as stratigraphical index taxa and may be helpful in the recognition and correlation of the Global Stage boundaries in the Lower and Middle Ordovician. The first appearance datum (FAD) of some 17 taxa, the taxonomy of which has been thoroughly reviewed in recent years, are plotted in this study against the British and Chinese graptolite zonations (Figure 1), following similar treatment of the FADs of 8 taxa by Brocke et al. (1995). The last appearance datum (LAD) of these taxa is more problematical, as palynomorphs of the size of the acritarchs may be reworked into younger sediments. LADs may be suggested with confidence in some instances, but only after a consistent pattern of occurrence has been determined from large data sets.